Perception of local communities on the indicators of governance in Tanjung Piai National Park - Kunasekaran, Puvaneswaran; Rozak, Nurul Izatul Natasya; Mohd Adam, Syamimi; Shuib, Ahmad (Universiti Malaysia Sarawak, 2018)
Concerned with the rapid depletion of mangrove and wetland ecosystems in Tanjung Piai National Park, a RAMSAR site, Johore, relevant government agencies are usually created and given the responsibilities to ensure that the establishment of these protected areas will achieve their objective of protecting the ecosystem, which are of national and perhaps, international interests. This paper discusses the perception of local community of Tanjung Piai, on role of good governance and community participation as tools to make environmental enforcement happen in Tanjung Piai National Park (TPNP). The findings of this research are based on structured questionnaires, measured using Likert scale. They are categorised into seven dimensions: Indicators of Governance, Management and Administration, Information and Knowledge, Policy and Plan, Environmental and Natural Resources, Facility and Infrastructure, and Finance and Budget. Factor Analysis is used in this study to regroup questions that are significant to this research, while Multiple Linear Regression Analysis is used to determine the factor affecting local community’s perception on governance roles. By using Descriptive Analysis, the percentage and frequency of socio-demographics, and the mean for dependent and independent variables are laid out to display the overall distribution of data. With regard to a valid analysis reference, the study’s outcome could be the deciding factor in choosing good governance guidelines for wetlands conservation that involves the participation of local community. Therefore, to achieve conservation of wetlands, proper governance is recommended and better enforcement of the law is needed.